Tyrosine kinases in nodal peripheral T-cell lymphomas - Piccaluga, Pier Paolo; Cascianelli, Chiara; Inghirami, Giorgio (Frontiers in Oncology, 2023)
Nodal peripheral T-cell lymphomas (PTCL) are uncommon and heterogenous tumors, overall characterized by a dismal prognosis. Targeted therapy has been then proposed. However, so far reliable targets at mostly represented by a few surface antigens (e.g. CD52 and CD30), chemokine receptor (e.g. CCR4) and epigenetic regulation of gene expression. In the last 2 decades, however, several evidence supported the idea that tyrosine kinases (TK) deregulation might be relevant for both pathogenesis and treatment of PTCL. Indeed, they can be expressed/activated a s a consequence of their involvement in genetic lesions, such as translocations, or by ligands overexpression. The most striking example is represented by ALK in anaplastic large cell lymphomas (ALCL). ALK activity, in fact, is necessary to support cell proliferation and survival, its inhibition leading to cell death. Of note STAT3 was indicated as the main downstream of ALK. More recently, other TK have been shown to be consistently expressed and active in PTCLs, like PDGFRA and member of T-cell receptor signaling like SYK. Noteworthy, as in the case of ALK, STAT proteins emerged as key downstream factors for most of the involved TK. In this article the authors review the most critical findings about TK in nodal PTCL, based on their own experience as well as on the most updated literayture.